Promoting Digital Literacy Through Social Media: Enhancing Unity and Resilience in Indonesia’s Election Discourse - King Anugrah Wiguna; Rita Gani; Citra Rosalyn Anwar; Yohannes Adven Sarbani; Niken Puppy Setyawati (CHANNEL: Jurnal Komunikasi, 2025)
Social media is defined as the ideal platform for creating a new public space where information, agendas, and public discourse can meet. In Indonesia, the threat to social media as a public space arises from the proliferation of misinformation, disinformation, and malinformation. This threat becomes particularly evident during election periods. In a democratic society, elections serve as a moment for exchanging aspirations, ideas, and public discourse. Therefore, it is crucial to ensure initiatives that promote unity and digital resilience through social media. This study aims to describe the forms of digital literacy and critical thinking education conducted by Tular Nalar on social media using a qualitative approach. The study analyzes how social media content, as a medium for promoting digital literacy and critical thinking education, can drive unity and digital resilience during election periods. Using content analysis, this research explores the types of content Tular Nalar shares on Instagram. The findings show that using Dialoguer and the Relevance strategy allows Tular Nalar’s social media content to reach its audience effectively. To improve engagement and critical awareness among first-time voters, educators and digital campaigners should use dialogic, relevance-based content. From a policy standpoint, the findings could help organizations like Kominfo, KPU, and Bawaslu create inclusive, participatory, and context-sensitive campaigns to counter false information and bolster digital resilience during election seasons by informing national digital literacy frameworks and election communication guidelines.